The Role of Transformational Leadership in Improving Employee Performance Through A High-Performance Work System As A Mediation - Winarto, Abraham Jordy; Mas'ud, Fuad (Yayasan Riset dan Pengembangan Intelektual, 2025)
Optimal employee performance is a crucial aspect in the banking industry, which is characterized by high pressure, demanding targets, and complex service processes. Bank Mandiri, as one of the largest banks in Indonesia, faces ongoing challenges in maintaining superior human resource performance within an increasingly dynamic and competitive environment. In this context, leadership and work systems play a vital role in supporting both individual and organizational performance. This study aims to examine the role of transformational leadership in enhancing employee performance through the implementation of a high-performance work system (HPWS) and the facilitation of knowledge sharing as mediating variables. The study adopts a quantitative explanatory approach, with data collected through questionnaires distributed to employees of Bank Mandiri in Semarang City. Data were analyzed using Structural Equation Modeling (SEM) with the support of AMOS software. The findings indicate that transformational leadership positively influences employee performance and the implementation of HPWS. HPWS is also found to have a positive effect on employee performance and knowledge sharing, while knowledge sharing contributes positively to employee performance. Furthermore, the results demonstrate that HPWS plays a significant mediating role in the relationship between transformational leadership and employee performance. The combined mediation of HPWS and knowledge sharing further strengthens this relationship. Overall, these findings highlight the importance of effective leadership, well-designed work systems, and a strong knowledge-sharing culture in optimizing employee performance within the banking sector.